2021
DOI: 10.3389/fpls.2021.712179
|View full text |Cite
|
Sign up to set email alerts
|

Expression Elements Derived From Plant Sequences Provide Effective Gene Expression Regulation and New Opportunities for Plant Biotechnology Traits

Abstract: Plant biotechnology traits provide a means to increase crop yields, manage weeds and pests, and sustainably contribute to addressing the needs of a growing population. One of the key challenges in developing new traits for plant biotechnology is the availability of expression elements for efficacious and predictable transgene regulation. Recent advances in genomics, transcriptomics, and computational tools have enabled the generation of new expression elements in a variety of model organisms. In this study, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…Recent studies have also shown the potential for fine‐tuning transgene expression levels by regulatory elements while spatiotemporal specificity is preserved [37,72,7779]. In order to achieve quantitative expression at various levels, a rational design by combining multiple regulatory elements from various species, such as the core promoters, enhancers, 5′UTR, 3′UTR, and introns, was used to construct expression cassettes with quantitative intensities in multiple species and tissues [54,57,68,80,81]. The theoretical transcriptional activity (TTA) of cassettes with different promoter/terminator combinations is coincident with the experimental activity values in transiently transformed Nicotiana leaves [56].…”
Section: Quantitative Plant Synthetic Biology Is Emergingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have also shown the potential for fine‐tuning transgene expression levels by regulatory elements while spatiotemporal specificity is preserved [37,72,7779]. In order to achieve quantitative expression at various levels, a rational design by combining multiple regulatory elements from various species, such as the core promoters, enhancers, 5′UTR, 3′UTR, and introns, was used to construct expression cassettes with quantitative intensities in multiple species and tissues [54,57,68,80,81]. The theoretical transcriptional activity (TTA) of cassettes with different promoter/terminator combinations is coincident with the experimental activity values in transiently transformed Nicotiana leaves [56].…”
Section: Quantitative Plant Synthetic Biology Is Emergingmentioning
confidence: 99%
“…Machine learning (ML) algorithms, such as support vector machine (SVM) or neural networks, greatly facilitate the qualitative/quantitative prediction and de novo design of bioparts. Sequence motifs identified by POsition‐sensitive WoRd Set (POWERS) algorithm are used to generate novel elements, whose property of expression is comparable to plant native elements across multiple tissues and developmental stages [81,82]. Another way to obtain customizable elements is de novo design.…”
Section: Quantitative Plant Synthetic Biology Is Emergingmentioning
confidence: 99%